STUDI KEPEMIMPINAN KEPALA BIRO DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA PADA BIRO HUBUNGAN MASYARAKAT SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Mohamad Aditya Rahman; Aji Ratna Kusuma; Erwin Resmawan (Jurnal Paradigma (JP), 2019)
This study is aimed to describe, analyze and to interpret the Head of Leadership Study Bureau in Improving the Performance of State Civil Apparatus at the Public Relations Bureau of the Regional Secretariat of East Kalimantan Province. This research uses a qualitative approach. The data obtained is done by using in-depth interviews, observations, and supporting data/documentation, which are then analyzed using an interactive analysis model through the stage of data condensation, data presentation, conclusions. The results of the study show that the function of the innovator, the function of communicators, the function of the motivator, the function of the controller has not been maximizedKeywords: Leadership, Performance, Function, State Civil Apparatus.